Breaking yield barriers in pearlmillet (Pennisetum glaucum)-wheat (Triticum aestivum) cropping system through agronomic operations in semi-arid Haryana - Kumar, Pawan; Yadav, S K; Kumar, Manoj; Rinwa, R S; Singh, K P (The Indian Journal of Agricultural Sciences, 2007)
A field experiment was conducted during 2003-05 at Hisar to study the response of pearlmillet (Pennisetum glaucum (L.) R. Br. emend. Stuntz)-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system to farmyard manure and increased seed rate. Incorporation of 10 tonnes/ha farmyard manure in pearlmillet increased grain yield of both pearlmillet and wheat, net return, evapotranspiration and water-use efficiency over the recommended dose of fertilizers to both crops. Incorporation of farmyard manure in pearlmillet and 30% higher seed rate to pearlmillet and wheat increased all parameters, viz grain yield of pearlmillet and wheat (9.88 and 4.26 %), net return (13.66 and 6.33 %), evapotranspiration (4.85 and 2.58 %) and water-use efficiency (4.95 and 1.66 %) over both recommended fertilizers application alone or with 10 tonnes farmyard manure to pearlmillet.